Peningkatan Pengetahuan Kepala Ruangan dalam Mengelola Strategi Gaya Manajemen Konflik Untuk Meningkatkan Kinerja Perawat - Conny Oktizulvia; Asmawati (Universitas Alifah Padang, 2025)
Conflict in the nursing environment is an unavoidable phenomenon that has a direct impact on nurses' performance. The head nurse plays an important role in managing conflict to prevent it from negatively impacting performance and the quality of nursing care. This Community Service activity aims to increase the knowledge and understanding of nurse managers, especially head nurses, regarding conflict management style strategies as an effort to support improved performance of implementing nurses at Hospital in Padang. The activity will be held on August 28, 2025, using interactive lecture-based talks with question-and- answer discussions and evaluations in the form of pre-tests and post-tests. A total of 15 nurse managers with the position of head nurse will participate in this activity. Evaluation was conducted through pre-tests and post-tests using an instrument to assess knowledge about conflict management styles. The results of the activity show an increase in the average knowledge score from 10.47 (pre-test) to 14.53 (post-test), representing an increase of 38.7% with a p-value of 0.001 (p<0.05). These results indicate that educational activities are able to improve nurse managers' understanding of conflict management styles strategies, which is expected to impact improved performance and a harmonious work environment in nursing. This education is effective in increasing participants' understanding of the application of conflict management strategies, which is expected to support a more harmonious work environment and optimal nursing performance.